(untitled) (Innovative professional education, 2024)
The article reveals the essence of the concept of "self-sufficiency" as a multidisciplinary multilevel phenomenon associated with the ability of a certain individual or collective subject to "cope with themselves". The importance of self-sufficiency for the development of youth entrepreneurship and post-war economic recovery is substantiated.